Utilization of Artificial Intelligence in Improving Products and Services of Bank Syariah Indonesia (BSI) in Tanjung Balai in the Era of Society 5.0 - Fanny Julia Putri; Bi Rahmani, Nur Ahmadi; Syahriza, Rahmi (JURNAL MANAJEMEN MOTIVASI, 2026)
This study analyzes the use of Artificial Intelligence (AI) to improve products and services at Bank Syariah Indonesia (BSI) in Tanjung Balai in the Society 5.0 era. Using a qualitative approach involving field observations, employee interviews, and document review, the study finds that AI can enhance product personalization, accelerate customer service through chatbots and automated data analysis, and strengthen risk management and transaction security. However, implementation faces challenges related to infrastructure, human resources, data integration, and customer digital literacy. Sharia compliance requires human and supervisory oversight. Thus, AI can support inclusive and welfare-oriented Sharia banking transformation. Keywords: Artificial Intelligence; Bank Syariah Indonesia; Service Quality; Product Innovation; Digital Transformation; Sharia Compliance